1986
DOI: 10.1093/ije/15.2.218
|View full text |Cite
|
Sign up to set email alerts
|

Mortality among Koreans living in Osaka, Japan, 1973–1982

Abstract: The mortality pattern of Koreans living in Osaka, Japan was surveyed by comparing their age-specific and age-adjusted death rates with those among Japanese during 1973-1982. Cancer was the leading cause of death among Korean males, while cerebrovascular disease was most common among Korean females in Osaka. Mortality rates from tuberculosis, cancer, mental disorder, cerebrovascular disease, chronic obstructive pulmonary diseases (COPD), liver cirrhosis, accidents and suicide were significantly higher for Korea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1987
1987
2007
2007

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Precipitating factors were suggested to be the high prevalence of hepatitis C and B virus carriers, and heavy drinkers among Koreans in Osaka. Investigations of health problems among Koreans in Japan have mainly focused on age‐adjusted mortality rates 8–11 and the prevalence of liver diseases 12,13 . Previous socioeconomic research revealed that financial difficulties are common among Korean elderly 14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…Precipitating factors were suggested to be the high prevalence of hepatitis C and B virus carriers, and heavy drinkers among Koreans in Osaka. Investigations of health problems among Koreans in Japan have mainly focused on age‐adjusted mortality rates 8–11 and the prevalence of liver diseases 12,13 . Previous socioeconomic research revealed that financial difficulties are common among Korean elderly 14,15 .…”
Section: Introductionmentioning
confidence: 99%